2017
DOI: 10.1097/md.0000000000007659
|View full text |Cite
|
Sign up to set email alerts
|

The effect of topical thiocolchicoside in preventing and reducing the increase of muscle tone, stiffness, and soreness

Abstract: In professional road cyclists, the majority of overuse injuries affect the lower limbs and are mostly represented by contractures or muscle shortening, characterized by an increase of tone and stiffness and a variation of elasticity. Treatment and prevention of these specific conditions may include physical, supplementary, and pharmacologic support. The aim of this real-life study was to determine: first, the alterations of tone, stiffness, elasticity, and soreness of rectus femoris (RF) and biceps femoris (BF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…In this regard, tone and stiffness are two parameters expressing the viscoelastic state of living tissues (muscles and tendons), which have been shown to reflect their biomechanical/functional status and integrity [ 14 , 27 ]. The tone and stiffness values augment with the increase of the contraction levels, exhaustive activity, and ageing [ 28 , 29 ]. Recently Morgan et al [ 30 ] and Finnamore et al [ 16 ] reported that AT induces appreciable alterations in Achilles tendon viscoelasticity suggesting a correlation between tendon integrity and its viscoelastic properties.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, tone and stiffness are two parameters expressing the viscoelastic state of living tissues (muscles and tendons), which have been shown to reflect their biomechanical/functional status and integrity [ 14 , 27 ]. The tone and stiffness values augment with the increase of the contraction levels, exhaustive activity, and ageing [ 28 , 29 ]. Recently Morgan et al [ 30 ] and Finnamore et al [ 16 ] reported that AT induces appreciable alterations in Achilles tendon viscoelasticity suggesting a correlation between tendon integrity and its viscoelastic properties.…”
Section: Discussionmentioning
confidence: 99%
“…95 Therefore more research is required. [94][95][96] It does not appear if there is a role for SMRs as part of combination management for acute cervical strains [80][81] , post-exercise muscle soreness [87][88] , or myofascial pain syndrome [110][111][112][113][114][115][116] but again more research is required. 117 The page number in the footer is not for bibliographic referencing www.tandfonline.com/oemd 13…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the single-axis accelerometer in the Myoton-2 and Myoton-3 devices, the MyotonPRO device has a tri-axial accelerometer, making it more versatile in terms of application [7]. Investigators in various fields have used the device, including in sport medicine [8,9], rehabilitation [10], and spaceflight [11]. Previous studies have shown that the MyotonPRO can reliably assess stiffness of MG, the lateral head of the gastrocnemius (LG), AT, and plantar fascia (PF) [1214].…”
Section: Introductionmentioning
confidence: 99%